Conductive PET composite material and preparation method thereof
By adding specific conductive fillers to PET, the problem of poor conductivity of PET composites is solved, which significantly improves its conductivity and physical and mechanical properties, and expands the scope of application.
Patent Information
- Application Number
- CN202411961703.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-30
Smart Images

Figure BDA0005217327250000101
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials, and in particular relates to a conductive PET composite material and a preparation method thereof. Background Art
[0002] Polyethylene terephthalate (PET) is the most important type of thermoplastic polyester, commonly known as polyester resin. It is made by ester exchange of dimethyl terephthalate with ethylene glycol or esterification of terephthalic acid with ethylene glycol to synthesize dihydroxyethyl terephthalate, and then polycondensation reaction. PET is a milky white or light yellow, highly crystalline polymer with a smooth and glossy surface. It has excellent physical and mechanical properties in a wide temperature range and can be used at a temperature of up to 120°C. PET is resistant to oil, fat, dilute acid, dilute alkali, and most solvents. Although the comprehensive performance of PET is very excellent, the conductivity of PS is average, which greatly limits the application range of PET composite materials. Summary of the invention
[0003] In view of the deficiencies in the prior art, the object of the present invention is to provide a conductive PET composite material and a preparation method thereof. The present invention adds specific conductive fillers to PET to make PET have excellent conductive properties.
[0004] The objective of the present invention is achieved through the following technical solutions:
[0005] A conductive PET composite material is made of the following components in parts by weight:
[0006] PET 92 parts - 102 parts,
[0007] Conductive filler 12-16 parts,
[0008] Antioxidant 0.1-0.5 parts;
[0009] The preparation method of the conductive filler is as follows:
[0010] S1. Place dopamine hydrochloride, Tris buffer solution, fullerene, ethanol and deionized water in a reaction vessel and mix them evenly, then place them in a temperature of 60-80° C. to react for 8-12 hours. The reaction solution is filtered to obtain a solid. The solid is washed and placed in a vacuum drying oven at 70-80° C. to dry for 6-10 hours to obtain dopamine-modified fullerene.
[0011] S2. Place tin chloride, ammonia water, ethanol and deionized water in a reaction vessel, mix well, place at 50-70°C for reaction for 10-12h, filter the reaction solution to obtain a solid, wash the solid and place in a vacuum drying oven at 60-80°C for drying for 12-16h to obtain solid A.
[0012] S3. The solid A is placed in a muffle furnace at 720-760° C. and calcined for 20-24 hours to obtain tin oxide.
[0013] S4. Place tin oxide, N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane, ethanol and deionized water in a reaction vessel and mix well, then place the mixture at 40-50°C to react for 12-14 hours. Filter the reaction solution to obtain a solid. Wash the solid and dry it in a vacuum drying oven at 50-70°C for 8-16 hours to obtain N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide.
[0014] S5. Place dopamine-modified fullerene, N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide, ethanol and deionized water in a reaction vessel and mix them evenly, then place them at 30-50°C to react for 6-10 hours. The reaction solution is filtered to obtain a solid. The solid is washed and placed in a vacuum drying oven at 60-70°C to dry for 8-12 hours to obtain a dopamine-modified fullerene / N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide type conductive filler.
[0015] Preferably, the mass ratio of dopamine hydrochloride, Tris buffer, fullerene, ethanol and deionized water in step S1 is (16-20): (24-30): (40-50): (60-80): (80-120).
[0016] Preferably, the mass ratio of tin chloride, ammonia water, ethanol and deionized water in step S2 is (20-30): (24-30): (50-60): (70-80).
[0017] Preferably, the mass ratio of tin oxide, N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane, ethanol and deionized water in step S4 is (24-30):(8-12):(60-70):(80-90).
[0018] Preferably, the mass ratio of dopamine-modified fullerene, N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide, ethanol, and deionized water in step S5 is (26-30): (28-32): (50-56): (70-80).
[0019] In a further embodiment, the antioxidant is at least one of tris(2,4-di-tert-butyl)phenyl phosphite (referred to as Irganox168), pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (referred to as Irganox1010), and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (referred to as Irganox1330).
[0020] The present invention also provides a method for preparing the conductive PET composite material, comprising the following steps:
[0021] (1) Weigh 92-102 parts of PET, 12-16 parts of conductive filler, and 0.1-0.5 parts of antioxidant and mix them evenly to obtain a mixture;
[0022] (2) Extruding the mixed material obtained in step (1) from a twin-screw extruder to form granules, thus obtaining a conductive PET composite material. Further, the twin-screw extruder comprises six temperature zones arranged in sequence, and the temperatures of the zones are: zone 1 temperature 240-260°C, zone 2 temperature 280-300°C, zone 3 temperature 280-300°C, zone 4 temperature 280-300°C, zone 5 temperature 280-300°C, zone 6 temperature 280-300°C; the head temperature of the twin-screw extruder is 280-300°C, and the screw speed is 200-280r / min.
[0023] The beneficial effects of the present invention are as follows:
[0024] (1) The chemical formula for preparing tin oxide in this patent is as follows:
[0025] NH3·H2O→NH4 + +OH -
[0026] Sn 4+ +4OH - →Sn(OH)4
[0027] Sn(OH)4→SnO2+2H2O.
[0028] (2) This patent first synthesizes a dopamine-modified fullerene, and then synthesizes an N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide. Because the catechol groups on the surface of the modified fullerene can hydrogen bond with the amino groups in the methoxysilane groups on the surface of the modified tin oxide, a dopamine-modified fullerene / N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide type conductive filler is formed.
[0029] (3) The dimethoxysilyl group in N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane can chemically bond with the oxygen atoms on the surface of tin oxide, thereby enhancing the bonding strength between N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane and tin oxide.
[0030] (4) The conductive filler of the present invention comprises dopamine and N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane, wherein dopamine comprises a catechol group, and N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane comprises methoxysilane. These groups improve the interfacial compatibility between the conductive filler and PET, and are beneficial to the dispersibility of the conductive filler in PET, thereby facilitating the improvement of the conductive properties and physical properties of the PET composite material. The PET composite material prepared by the present invention has excellent conductivity and physical and mechanical properties, and has great promotion significance. DETAILED DESCRIPTION
[0031] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0033] The raw materials used in the following examples are as follows:
[0034] PET (model 008L), Aclo, Canada; Tris buffer, Hubei Keward Chemical Co., Ltd.; ammonia, Shandong Baihua Chemical Co., Ltd.; ethanol, Jinan Mingxin Chemical Co., Ltd.; fullerene, Wuhan Jushun Chemical Co., Ltd.; tin chloride, Wuhan Jiyesheng Chemical Co., Ltd.; N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane, Nanjing Aocheng Chemical Co., Ltd.; dopamine hydrochloride, Hubei Ruiboxin Chemical Co., Ltd.; deionized water, Shanghai Lanyi Environmental Protection Technology Co., Ltd.; fullerene, Puyang Yongxin Fullerene Technology Co., Ltd.; tin oxide, Shijiazhuang Dongming New Materials Co., Ltd.; antioxidants (models Irganox168, Irganox1010, Irganox1330), BASF, Germany.
[0035] The above reagents are only used to illustrate the sources and components of the reagents used in the experiments of the present invention so as to fully disclose the information, and do not mean that the present invention cannot be achieved by using other similar reagents or reagents provided by other suppliers.
[0036] Preparation Example 1
[0037] S1. 160 g dopamine hydrochloride, 240 g Tris buffer solution, 400 g fullerene, 600 g ethanol and 800 g deionized water were placed in a reaction vessel and mixed evenly, and then placed at 60° C. to react for 8 h. The reaction solution was filtered to obtain a solid. The solid was washed and dried in a vacuum drying oven at 70° C. for 6 h to obtain dopamine-modified fullerene.
[0038] S2. Place 200 g of tin chloride, 240 g of ammonia water, 500 g of ethanol and 700 g of deionized water in a reaction vessel, mix well, and react at 50°C for 10 h. Filter the reaction solution to obtain a solid. Wash the solid and dry it in a vacuum drying oven at 60°C for 12 h to obtain solid A.
[0039] S3. The solid A is placed in a muffle furnace and calcined at 720° C. for 20 h to obtain tin oxide.
[0040] S4. Place 240 g of tin oxide, 80 g of N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane, 600 g of ethanol, and 800 g of deionized water in a reaction vessel and mix them evenly. Then place them at 40°C to react for 12 hours. The reaction solution is filtered to obtain a solid. The solid is washed and dried in a vacuum drying oven at 50°C for 8 hours to obtain N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide.
[0041] S5. Place 260 g of dopamine-modified fullerene, 280 g of N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide, 500 g of ethanol, and 700 g of deionized water in a reaction vessel and mix them evenly. Place the mixture at 30°C to react for 6 hours. Filter the reaction solution to obtain a solid. Wash the solid and dry it in a vacuum drying oven at 60°C for 8 hours to obtain a conductive filler M1 of dopamine-modified fullerene / N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide type.
[0042] Example 1
[0043] (1) Weigh 92 parts of PET, 12 parts of conductive filler M1, and 0.1 parts of Irganox 168, mix and stir evenly to obtain a mixture;
[0044] (2) The mixed material obtained in step (1) is extruded and granulated to obtain the PET composite material P1.
[0045] The temperatures and screw speeds of each zone of the twin-screw extruder are: zone 1 temperature 240°C, zone 2 temperature 280°C, zone 3 temperature 280°C, zone 4 temperature 280°C, zone 5 temperature 280°C, zone 6 temperature 280°C, die head temperature 280°C, and screw speed 200r / min.
[0046] Preparation Example 2
[0047] S1. Place 200 g dopamine hydrochloride, 300 g Tris buffer solution, 500 g fullerene, 800 g ethanol and 1.2 kg deionized water in a reaction vessel, mix well, and place at 80°C to react for 12 h. The reaction solution is filtered to obtain a solid. The solid is washed and dried in a vacuum drying oven at 80°C for 10 h to obtain dopamine-modified fullerene.
[0048] S2. Place 300 g of tin chloride, 300 g of ammonia water, 600 g of ethanol and 800 g of deionized water in a reaction vessel, mix them evenly, and then place them at 70°C to react for 12 hours. The reaction solution is filtered to obtain a solid. The solid is washed and dried in a vacuum drying oven at 80°C for 16 hours to obtain solid A.
[0049] S3. The solid A is placed in a muffle furnace and calcined at 760° C. for 24 hours to obtain tin oxide.
[0050] S4. Place 300 g of tin oxide, 120 g of N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane, 700 g of ethanol, and 900 g of deionized water in a reaction vessel and mix them evenly, then place them at 50°C to react for 14 hours. The reaction solution is filtered to obtain a solid. The solid is washed and dried in a vacuum drying oven at 70°C for 16 hours to obtain N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide.
[0051] S5. Place 300 g of dopamine-modified fullerene, 320 g of N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide, 560 g of ethanol, and 800 g of deionized water in a reaction vessel and mix them evenly. Place the mixture at 50°C to react for 10 hours. Filter the reaction solution to obtain a solid. Wash the solid and dry it in a vacuum drying oven at 70°C for 12 hours to obtain a conductive filler M2 of dopamine-modified fullerene / N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide type.
[0052] Example 2
[0053] (1) Weigh 102 parts of PET, 16 parts of conductive filler M2, 0.1 parts of Irganox 168, 0.2 parts of Irganox 1010, and 0.2 parts of Irganox 1330, mix and stir evenly to obtain a mixture;
[0054] (2) The mixed material obtained in step (1) is extruded and granulated to obtain the PET composite material P2.
[0055] The temperature and screw speed of each zone of the twin-screw extruder are: zone 1 temperature 260°C, zone 2 temperature 300°C, zone 3 temperature 300°C, zone 4 temperature 300°C, zone 5 temperature 300°C, zone 6 temperature 300°C, die head temperature 300°C, and screw speed 280r / min.
[0056] Preparation Example 3
[0057] S1. Place 180 g dopamine hydrochloride, 270 g Tris buffer solution, 450 g fullerene, 700 g ethanol and 1.0 kg deionized water in a reaction vessel and mix well, then place the mixture at 70° C. to react for 10 h. Filter the reaction solution to obtain a solid. Wash the solid and place the solid in a vacuum drying oven at 75° C. to dry it for 8 h to obtain dopamine-modified fullerene.
[0058] S2. Place 250 g of tin chloride, 270 g of ammonia water, 550 g of ethanol and 750 g of deionized water in a reaction vessel and mix them evenly, then place them at 60° C. to react for 11 hours. The reaction solution is filtered to obtain a solid. The solid is washed and dried in a vacuum drying oven at 70° C. for 14 hours to obtain solid A.
[0059] S3. The solid A is placed in a muffle furnace at 740° C. and calcined for 22 h to obtain tin oxide.
[0060] S4. Place 270 g of tin oxide, 100 g of N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane, 650 g of ethanol, and 850 g of deionized water in a reaction vessel and mix them evenly, then place them at 45°C to react for 13 hours. The reaction solution is filtered to obtain a solid. The solid is washed and dried in a vacuum drying oven at 60°C for 12 hours to obtain N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide.
[0061] S5. Place 280 g of dopamine-modified fullerene, 300 g of N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide, 530 g of ethanol, and 750 g of deionized water in a reaction vessel and mix them evenly. Place the mixture at 40°C to react for 8 hours. Filter the reaction solution to obtain a solid. Wash the solid and dry it in a vacuum drying oven at 65°C for 10 hours to obtain a conductive filler M3 of dopamine-modified fullerene / N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide type.
[0062] Example 3
[0063] (1) Weigh 97 parts of PET, 14 parts of conductive filler M3, 0.1 parts of Irganox 168, and 0.2 parts of Irganox 1010, mix and stir to obtain a mixture;
[0064] (2) The mixed material obtained in step (1) is extruded and granulated to obtain the PET composite material P3.
[0065] The temperatures and screw speeds of each zone of the twin-screw extruder are: zone 1 temperature 250°C, zone 2 temperature 290°C, zone 3 temperature 290°C, zone 4 temperature 290°C, zone 5 temperature 290°C, zone 6 temperature 290°C, die head temperature 290°C, and screw speed 240r / min.
[0066] Preparation Example 4
[0067] S1. Place 165 g dopamine hydrochloride, 255 g Tris buffer solution, 435 g fullerene, 715 g ethanol and 1.15 kg deionized water in a reaction vessel and mix well, then place the mixture at 78 ° C for 11 h. Filter the reaction solution to obtain a solid. Wash the solid and place the solid in a vacuum drying oven at 73 ° C for 9 h to obtain dopamine-modified fullerene.
[0068] S2. Place 225 g of tin chloride, 265 g of ammonia water, 535 g of ethanol and 745 g of deionized water in a reaction vessel and mix well, then place the mixture at 68°C for reaction for 11 h. Filter the reaction solution to obtain a solid. Wash the solid and dry it in a vacuum drying oven at 76°C for 14.5 h to obtain solid A.
[0069] S3. The solid A was calcined in a muffle furnace at 735° C. for 23 h to obtain tin oxide.
[0070] S4. Place 275 g of tin oxide, 95 g of N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane, 635 g of ethanol, and 845 g of deionized water in a reaction vessel and mix well, then place the mixture at 48°C to react for 13.5 hours. The reaction solution is filtered to obtain a solid. The solid is washed and dried in a vacuum drying oven at 58°C for 14 hours to obtain N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide.
[0071] S5. Place 295 g of dopamine-modified fullerene, 315 g of N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide, 535 g of ethanol, and 735 g of deionized water in a reaction vessel and mix well, then place the mixture at 45°C to react for 8.5 hours. Filter the reaction solution to obtain a solid. Wash the solid and dry it in a vacuum drying oven at 66°C for 11 hours to obtain a conductive filler M4 of dopamine-modified fullerene / N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide type.
[0072] Example 4
[0073] (1) Weigh 95 parts of PET, 15 parts of conductive filler M4, 0.1 parts of Irganox 1010, and 0.2 parts of Irganox 1330, mix and stir evenly to obtain a mixture;
[0074] (2) The mixed material obtained in step (1) is extruded and granulated to obtain the PET composite material P4.
[0075] The temperatures and screw speeds of each zone of the twin-screw extruder are: zone 1 temperature 245°C, zone 2 temperature 285°C, zone 3 temperature 285°C, zone 4 temperature 285°C, zone 5 temperature 285°C, zone 6 temperature 285°C, die head temperature 285°C, and screw speed 255r / min.
[0076] Preparation Example 5
[0077] S1. Place 188 g dopamine hydrochloride, 255 g Tris buffer solution, 435 g fullerene, 645 g ethanol and 925 g deionized water in a reaction vessel and mix well, then place the mixture at 77°C for reaction for 9.5 h. Filter the reaction solution to obtain a solid. Wash the solid and place the solid in a vacuum drying oven at 72°C for 9.5 h to obtain dopamine-modified fullerene.
[0078] S2. Place 288 g of tin chloride, 268 g of ammonia water, 535 g of ethanol and 745 g of deionized water in a reaction vessel and mix well, then place the mixture at 66° C. to react for 11.5 h. Filter the reaction solution to obtain a solid. Wash the solid and dry it in a vacuum drying oven at 76° C. for 14.5 h to obtain solid A.
[0079] S3. The solid A was placed in a muffle furnace and calcined at 758°C for 23.5 hours to obtain tin oxide.
[0080] S4. Place 255 g of tin oxide, 115 g of N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane, 655 g of ethanol, and 845 g of deionized water in a reaction vessel and mix well, then place the mixture at 48°C to react for 13.5 hours. The reaction solution is filtered to obtain a solid. The solid is washed and dried in a vacuum drying oven at 58°C for 14 hours to obtain N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide.
[0081] S5. Place 298 g of dopamine-modified fullerene, 315 g of N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide, 535 g of ethanol, and 765 g of deionized water in a reaction vessel and mix well, then place the mixture at 38°C to react for 9.5 hours. Filter the reaction solution to obtain a solid. Wash the solid and dry it in a vacuum drying oven at 66°C for 11.5 hours to obtain a conductive filler M5 of dopamine-modified fullerene / N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide type.
[0082] Example 5
[0083] (1) Weigh 100 parts of PET, 13 parts of conductive filler M5, 0.2 parts of Irganox 1010, and 0.2 parts of Irganox 1330, mix and stir to obtain a mixture;
[0084] (2) The mixed material obtained in step (1) is extruded and granulated to obtain the PET composite material P5.
[0085] The temperatures and screw speeds of each zone of the twin-screw extruder are: zone 1 temperature 250°C, zone 2 temperature 295°C, zone 3 temperature 295°C, zone 4 temperature 295°C, zone 5 temperature 295°C, zone 6 temperature 295°C, die head temperature 295°C, and screw speed 270r / min.
[0086] Comparative Example 1
[0087] (1) Weigh 100 parts of PET, 0.2 parts of Irganox 1010, and 0.2 parts of Irganox 1330, mix and stir to obtain a mixture;
[0088] (2) The mixed material obtained in step (1) is extruded and granulated to obtain the PET composite material D1.
[0089] The temperatures and screw speeds of each zone of the twin-screw extruder are: zone 1 temperature 250°C, zone 2 temperature 295°C, zone 3 temperature 295°C, zone 4 temperature 295°C, zone 5 temperature 295°C, zone 6 temperature 295°C, die head temperature 295°C, and screw speed 270r / min.
[0090] Comparative Example 2
[0091] (1) Weigh 100 parts of PET, 13 parts of tin oxide, 0.2 parts of Irganox 1010, and 0.2 parts of Irganox 1330, mix and stir to obtain a mixture;
[0092] (2) The mixed material obtained in step (1) is extruded and granulated to obtain the PET composite material D2.
[0093] The temperatures and screw speeds of each zone of the twin-screw extruder are: zone 1 temperature 250°C, zone 2 temperature 295°C, zone 3 temperature 295°C, zone 4 temperature 295°C, zone 5 temperature 295°C, zone 6 temperature 295°C, die head temperature 295°C, and screw speed 270r / min.
[0094] Comparative Example 3
[0095] (1) Weigh 100 parts of PET, 13 parts of fullerene, 0.2 parts of Irganox 1010, and 0.2 parts of Irganox 1330, mix and stir to obtain a mixture;
[0096] (2) The mixed material obtained in step (1) is extruded and granulated to obtain the PET composite material D3.
[0097] The temperatures and screw speeds of each zone of the twin-screw extruder are: zone 1 temperature 250°C, zone 2 temperature 295°C, zone 3 temperature 295°C, zone 4 temperature 295°C, zone 5 temperature 295°C, zone 6 temperature 295°C, die head temperature 295°C, and screw speed 270r / min.
[0098] Performance Test:
[0099] The surface resistivity of the materials prepared in each embodiment and comparative example was tested according to the test standard GB / T 31838.3, the tensile strength was tested according to ASTM D638, the flexural modulus was tested according to ASTM D790, and the Izod notched impact strength was tested according to ASTM D256. The test results are shown in Table 1 below:
[0100] Table 1
[0101]
[0102] It can be seen from the above table:
[0103] In general, the electrical conductivity of P1-P5 is significantly better than that of D1-D3, which indicates that the electrical conductivity of the PET composite material of the present invention is better.
[0104] The physical properties of P1-P5 are better than those of D1-D3, which indicates that the physical properties of the PET composite material of the present invention are better.
[0105] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0106] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A conductive PET composite material, characterized in that: Made from the following components in parts by weight: PET 92 parts - 102 parts, Conductive filler 12-16 parts, Antioxidant 0.1-0.5 parts; The conductive filler is a dopamine-modified fullerene / N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide type conductive filler.
2. The conductive PET composite material according to claim 1, characterized in that: The preparation method of the conductive filler is as follows: S1. Place dopamine hydrochloride, Tris buffer solution, fullerene, ethanol and deionized water in a reaction vessel and mix them evenly, then place them in a temperature of 60-80°C to react for 8-12 hours, filter the reaction solution to obtain a solid, wash the solid and place it in a vacuum drying oven at 70-80°C to dry it for 6-10 hours to obtain dopamine-modified fullerene; S2, tin chloride, ammonia water, ethanol and deionized water are placed in a reaction vessel and mixed evenly, and then placed in a temperature of 50-70°C for reaction for 10-12 hours, the reaction solution is filtered to obtain a solid, and the solid is washed and placed in a vacuum drying oven at 60-80°C for 12-16 hours to obtain solid A; S3, calcining solid A in a muffle furnace at 720-760° C. for 20-24 hours to obtain tin oxide; S4, placing tin oxide, N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane, ethanol, and deionized water in a reaction vessel, mixing them evenly, placing them at a temperature of 40-50° C. to react for 12-14 hours, filtering the reaction solution to obtain a solid, washing the solid, and placing it in a vacuum drying oven at 50-70° C. to dry it for 8-16 hours to obtain N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide; S5. Place dopamine-modified fullerene, N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide, ethanol and deionized water in a reaction vessel and mix them evenly, then place them at 30-50°C to react for 6-10 hours. The reaction solution is filtered to obtain a solid. The solid is washed and placed in a vacuum drying oven at 60-70°C to dry for 8-12 hours to obtain a dopamine-modified fullerene / N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide type conductive filler.
3. The conductive PET composite material according to claim 2, characterized in that: The mass ratio of dopamine hydrochloride, Tris buffer, fullerene, ethanol and deionized water in step S1 is (16-20):(24-30):(40-50):(60-80):(80-120).
4. The conductive PET composite material according to claim 2, characterized in that: The mass ratio of tin chloride, ammonia water, ethanol and deionized water in step S2 is (20-30): (24-30): (50-60): (70-80).
5. The conductive PET composite material according to claim 2, characterized in that: The mass ratio of tin oxide, N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane, ethanol and deionized water in step S4 is (24-30):(8-12):(60-70):(80-90).
6. The conductive PET composite material according to claim 2, characterized in that: The mass ratio of dopamine-modified fullerene, N-(β-aminoethyl)-γ-aminopropylmethyl-dimethoxysilane-modified tin oxide, ethanol, and deionized water in step S5 is (26-30):(28-32):(50-56):(70-80).
7. The conductive PET composite material according to claim 1, characterized in that: The antioxidant is at least one of tris(2,4-di-tert-butyl)phenyl phosphite, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, and 1,3,5-trimethyl-2,4,6-(3,5-di-tert-butyl-4-hydroxybenzyl)benzene.
8. The method for preparing the conductive PET composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Weigh 92-102 parts of PET, 12-16 parts of conductive filler, and 0.1-0.5 parts of antioxidant and mix them evenly to obtain a mixture; (2) Extruding the mixture obtained in step (1) through a twin-screw extruder to form granules, thereby obtaining a conductive PET composite material.
9. The method for preparing the conductive PET composite material according to claim 8, characterized in that: The twin-screw extruder includes six temperature zones arranged in sequence, and the temperatures of each zone are: zone one temperature 240-260°C, zone two temperature 280-300°C, zone three temperature 280-300°C, zone four temperature 280-300°C, zone five temperature 280-300°C, zone six temperature 280-300°C; the head temperature of the twin-screw extruder is 280-300°C, and the screw speed is 200-280r / min.
Citation Information
Patent Citations
Conductive friction-resistant bio-based PA46 composite material and preparation method thereof
CN117511190A
Antibacterial conductive PET composite material and preparation method thereof
CN118703025A
Antibacterial agent, and antibacterial polysulfone composite material and preparation method therefor
WO2023024661A1